Languages From the World of the Bible - Gzella, Holger (De Gruyter, 2011)
The alphabetic script is part of the lasting heritage of the ancient Near East. It unites a number of newly-emerging civilizations in ancient Syria-Palestine, which together constitute the immediate background of the Hebrew Bible. Transformed by the impact of Hellenism, they also shaped the social-historical and cultural setting of the New Testament. This work presents fresh and concise yet thorough overviews of the relevant languages and their interaction. They are informed by the most recent scholarship and share a clear historical framework.